2021
DOI: 10.3390/ijms22115445
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Role of Transcription Factors in Osteogenesis

Abstract: Bone is a dynamic tissue constantly responding to environmental changes such as nutritional and mechanical stress. Bone homeostasis in adult life is maintained through bone remodeling, a controlled and balanced process between bone-resorbing osteoclasts and bone-forming osteoblasts. Osteoblasts secrete matrix, with some being buried within the newly formed bone, and differentiate to osteocytes. During embryogenesis, bones are formed through intramembraneous or endochondral ossification. The former involves a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 189 publications
3
79
0
Order By: Relevance
“…Moreover, the PCL/LAP scaffold upregulated the expression of RUNX2, ALP and Col-1α1 in BMSCs. RUNX2, a transcription factor involved in bone formation, activates bone-specific gene transcription promoters (including ALP and Col-1α1 ) during the early stage of osteogenic differentiation [ 39 ]. Therefore, it is reasonable to presume that the PCL/LAP scaffold stimulated extracellular matrix mineralization by accelerating Col-1α1 synthesis to provide a matrix for osteoid formation, which might be attributed to the increased RUNX2 level induced by LAP released from PCL/LAP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PCL/LAP scaffold upregulated the expression of RUNX2, ALP and Col-1α1 in BMSCs. RUNX2, a transcription factor involved in bone formation, activates bone-specific gene transcription promoters (including ALP and Col-1α1 ) during the early stage of osteogenic differentiation [ 39 ]. Therefore, it is reasonable to presume that the PCL/LAP scaffold stimulated extracellular matrix mineralization by accelerating Col-1α1 synthesis to provide a matrix for osteoid formation, which might be attributed to the increased RUNX2 level induced by LAP released from PCL/LAP.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from osteoclasts containing miRNA-214 are delivered to osteoblasts through the ephrinA2-EphA2 signaling pathway and negatively regulate ATF4, thereby inhibiting osteogenic activity [ 102 ]. ATF4 is a crucial regulator of bone formation and determines the initiation and terminal differentiation of osteoblasts by transactivating the osteocalcin (OCN) gene and promoting the expression of other osteogenic genes, such as bone sialoprotein (BSP) and OSX [ 103 ]. In addition, lncRNA Hotair is classified as an essential regulator and is highly expressed in serum, which makes it a potential factor for the diagnosis of rheumatoid arthritis by serum assays [ 18 ].…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…In the present study, the results suggested that RUNX2 was highly expressed during the early stages of hDPSC osteoblast/odontoblastic differentiation following SAL treatment compared with the OM group. RUNX2 and OCN are two extensively studied osteoblast-specific transcription factors that are also key markers of osteoblastic cells ( 38 ). RUNX2 is typically expressed during early osteoblast differentiation and is indispensable for the differentiation and appropriate functioning of osteoblasts ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%